Germinación y emergencia de plántulas de cuatro especies de encino amenazadas - García-De La Cruz, Yureli; López-Barrera, Fabiola; Ramos-Prado, José María (Instituto de Ecología, A.C., 2016)
Germination and seedlingemergence of four endangered oak speciesGermination and emergence of the endangered cloud forest oak species Quercus germana, Q. insignis, Q. sartorii and Q. xalapensis were observed under different light conditions (sun vs. shade) in a secondary forest fragment (SFF) and in a greenhouse (GRE). Seed weight variability was evaluated for each species and its relationship to germination and emergence determined. After 60 days, a total of 62.17% of the acorns had germinated and 37.79% had emerged in both experiments. Germination was highest in Q. sartorii (71.83% ± 2.09%), followed by Q. germana (66.33% ± 2.06%), Q. insignis (60.83% ± 2.34%) and Q. xalapensis (53.50% ± 2.32%). In the GRE, Q. insignis germination was higher under sun (62.00% ± 4.73%) than shade (48.00% ± 5.12%), whereas its emergence was the lowest (37.66% ± 3.46%) compared to other species in both light environments. In the SFF, germination and emergence only differed among species; Q. xalapensis germination was lowest (47.00% ± 3.11%) and Q. sartorii emergence was highest (58.66% ± 3.35%), compared to the other species. Acorn weight did not influence germination or emergence in any species. The implications of this study are discussed, along with recommended propagation techniques for growing oaks for forest restoration in disturbed areas.